2008
DOI: 10.1371/journal.pone.0003389
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Role for 4qA/B in the Structural Rearrangement of the 4q35 Region and in the Regulation of FRG1 and ANT1 in Facioscapulohumeral Dystrophy

Abstract: The number of D4Z4 repeats in the subtelomeric region of chromosome 4q is strongly reduced in patients with Facio-Scapulo-Humeral Dystrophy (FSHD). We performed chromosome conformation capture (3C) analysis to document the interactions taking place among different 4q35 markers. We found that the reduced number of D4Z4 repeats in FSHD myoblasts was associated with a global alteration of the three-dimensional structure of the 4q35 region. Indeed, differently from normal myoblasts, the 4qA/B marker interacted dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 31 publications
9
58
0
Order By: Relevance
“…Previous studies had demonstrated that the D4Z4 enhancer could activate the FRG2 promoter (11,21) and that it physically interacts with the promoter region of FRG2 as well as that of DUX4c (23,24). Our present findings indicate that the D4Z4 enhancer is an efficient activator of the DUX4c promoter.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Previous studies had demonstrated that the D4Z4 enhancer could activate the FRG2 promoter (11,21) and that it physically interacts with the promoter region of FRG2 as well as that of DUX4c (23,24). Our present findings indicate that the D4Z4 enhancer is an efficient activator of the DUX4c promoter.…”
Section: Discussionsupporting
confidence: 71%
“…S1B). Analysis of the three-dimensional structure of the chromatin in this region has indicated that the D4Z4 enhancer directly contacts the FRG2 and DUX4c promoters (23,24). D4Z4 enhancer is also able to activate these promoters in vitro (this study and Ref.…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd)mentioning
confidence: 55%
See 1 more Smart Citation
“…Different findings obtained with 3C analysis described the formation of loops between other elements in the FSHD locus (DUX4c and the 4qA/B marker) and the FRG1 promoter . These data indicate that the tridimensional structure of the FSHD locus is complex and composite, probably more than one sequence elements (for example, D4Z4, DUX4c,4qA/B) or more than one chromatin modification factor might be required to obtain a fine regulation of FRG1 gene expression during muscle differentiation (Petrov et al, 2006;Pirozhkova et al, 2008).…”
Section: Long Distance Effect: a Repressor Complex Binding D4z4mentioning
confidence: 89%
“…Accumulating evidences indicate that gene regulation can be affected by physical interaction between two distant chromosomal regions in cis and in trans in mammalian cells (Tolhuis et al, 2002;Horike et al, 2005;Spilianakis et al, 2005;Lomvardas et al, 2006). Thus the DRC might exerts is inhibitory activity either modifying the chromatin structure or acting directly on 4q35 genes promoters through a physical interaction mediated by the formation of a cromatin loop (Gabellini et al, 2002;Pirozhkova et al, 2008). The physical interaction between D4Z4 and FRG1 has been demonstrated Bodega et al, 2009) in normal myoblast by Chromosome conformation capture (3C), which is a technique that identifies long distance intra-and inter-chromosomal interactions (Dekker et al, 2002).…”
Section: Long Distance Effect: a Repressor Complex Binding D4z4mentioning
confidence: 99%